Analisis Risiko Teknologi Informasi Menggunakan ISO 31000 pada Program HRMS - Stefan Agustinus; Adi Nugroho; Ariya Dwika Cahyono (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
The HRMS program is the central database of all matters relating to Human Resources Development of PT. XYZ. The existence of HRMS program is very important for the sustainability of the company, especially in the employment sector. Therefore, this HRMS program should be able to run optimally and consistently. A risk analysis is required to obtain documentation of the various possible risks that are in the vicinity of the HRMS program and the risk treatment required to minimize the likelihood of these risks arising. Risk analysis used at PT. XYZ is ISO 31000. The first stage used in this research is the stage of risk assessment which consisting of 3 stages, namely risk identification, risk analysis, and risk evaluation. The second stage is the stage of risk treatment. The results of this research are used as a tool for the stakeholders of the company to be able to arrange documentation related to company risk management in the future.